2017
DOI: 10.5812/ircmj.14531
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intravenous Infusion of Lidocaine to Control Postoperative Pain After Gynecologic Laparoscopic Surgery: A Randomized Double-Blind Placebo-Controlled Clinical Trial

Abstract: Background: Pain after laparoscopy may still be moderate to severe due to stretching of intraabdominal cavity and peritoneal inflammation. Systemic lidocaine with anti-inflammatory properties may reduce this pain. Objectives: The aim of this study was to evaluate the effect of perioperative intravenous infusion of lidocaine on postoperative pain relief after gynecologic laparoscopic procedure. Methods: A double-blind randomized clinical trial study was conducted in Iran, during years 2014 and 2015. A sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Also, another study in patients undergoing hip arthroplasty showed that continuous infusion of low dose lidocaine (1.5 mg/kg) compared to placebo, did not affect the pain intensity and reducing the opioid consumption after surgery [9]. The results of Moslemi et al on patients undergoing gynecologic laparoscopic surgery indicate that infusion of lidocaine (1.5 mg/kg) could significantly affect postoperative pain reduction [18]. Also, it has been shown that adding lidocaine to morphine PCA, compared to morphine PCA alone, has no significant efficacy in postoperative pain reduction after abdominal surgery [19].…”
Section: Discussionmentioning
confidence: 99%
“…Also, another study in patients undergoing hip arthroplasty showed that continuous infusion of low dose lidocaine (1.5 mg/kg) compared to placebo, did not affect the pain intensity and reducing the opioid consumption after surgery [9]. The results of Moslemi et al on patients undergoing gynecologic laparoscopic surgery indicate that infusion of lidocaine (1.5 mg/kg) could significantly affect postoperative pain reduction [18]. Also, it has been shown that adding lidocaine to morphine PCA, compared to morphine PCA alone, has no significant efficacy in postoperative pain reduction after abdominal surgery [19].…”
Section: Discussionmentioning
confidence: 99%